Evaluation of the Phase 2A IRT Network in respect to the Principles of Transport Justice - Parker, Taariq (Department of Civil Engineering, 2024)
The South African Transport system is inherently designed on transport inequities and spatial segregation. This is still evident in many cities and has not been completely addressed since the prior apartheid regime. Many lower income groups are still residing on the city outskirts, far away from potential job opportunities, including the central business district. These groups are disproportionately affected by the long travel times and consequently higher travel costs, resulting in a large percentage of their time and income being spent on transport. A high-quality public transport system with a broad catchment area is required to increase the access to opportunities, in an attempt to address the lingering inequalities of the past apartheid regime. There has been a focus in South African cities on bus rapid transit (BRT) as the future of public transport (PT) trunk services. Three key features that distinguish BRT systems from conventional bus systems are the improved infrastructure, operations, and technology. The key research objectives of this dissertation were:  To determine appropriate measures of accessibility in South Africa;  To identify a suitable accessibility threshold that can be used for comparison purposes; and  To evaluate the effectiveness of Cape Town's Integrated Rapid Transit (IRT) Phase 2A route in terms of transportation planning based on the principles of justice and the identified accessibility threshold. This study has focused on the approved Phase 2A route of Cape Town's Integrated Rapid Transit (IRT) system, which is currently being built, and did not analyse Phase 1 (which is already built) or Phases 3 and 4 (which are still planned for the future). As such, the study area consisted of the suburbs in the immediate vicinity of the proposed route and not the whole of Cape Town, namely, the Southern Suburbs and Metro Southeast. Due to the rail line not having a direct east-west route between these areas, the study focused on the road-based transport, i.e., private cars, minibus taxis (MBT) and Golden Arrow Bus Services (GABS). A simplified network model based on zones and road-based transport (as mentioned above) was built of the suburbs surrounding the IRT Phase 2A route using QGIS software. The model zones consist of the demographic data of the population. The existing public transport facilities, i.e. minibus taxis and Golden Arrow Bus Services, were outlined as nodes and links in the model. The model was run to determine travel times and speeds between zones. Potential Mobility Index (PMI) scores were calculated for each zone and used to determine origin to destination accessibility levels (number of jobs available). Using the chosen accessibility measures, the most underserved zones within the study area were identified. The IRT route was then evaluated against this to determine whether these areas would be sufficiently provided for, by plotting the potential accessibility of each TAZ based on the IRT catchment area. Based on the analysis results, it is evident that having access to a car will allow an individual access to most, if not all, jobs in the study area within a 30-minute period. This can be extrapolated and used to assume that similar patterns would be applicable to other trip purposes such as healthcare services, shopping, education, leisure etc., as well as during different times and days of the week. Those who rely on road-based public transport as their main mode will however be stuck with low levels of accessibility in all circumstances, and even worse in certain cases such as weekends and night-time when PT services are reduced. 2 In order to evaluate the compliance of Cape Town's Integrated Rapid Transit (IRT) Phase 2A route with transportation planning based on the principles of justice, various accessibility sufficiency thresholds were tested. The number of underserved reliant on public transport based on each of these thresholds that are serviced by the IRT Phase 2A route was used in this assessment. Based on the outcome of this assessment, it is anticipated that the underserved groups within the study area will be sufficiently serviced by the planned future IRT Phase 2A network. The large inequalities between those who are reliant on road-based public transport and those who have access to a car within the study area, and Cape Town as a whole, are evident in the outcomes of this study, and are exacerbated by the fact that the public transport system is generally inefficient and unreliable. The assessment of the proposed IRT Phase 2A network through the Southern Suburbs and Metro Southeast has also shown that this method of planning based on transport justice can be used as a tool to confirm whether decision makers are correctly choosing the best solution by which these underserved areas can be aided sufficiently. Transport planning has the potential to play a critical role in advancing social and economic justice in South Africa. By incorporating the principles of justice, transport planning can help to create more equitable and accessible transport systems for all members of society, including the previously disadvantaged. To support the implementation of transport justice, transportation planners must have a good understanding of the social, economic, and environmental impacts of their decisions. They should also have the knowledge, tools and skills to analyse and address transportation inequalities and implement equitable transportation solutions